2008
DOI: 10.1128/iai.00427-08
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coliDraE Adhesin-Associated Bacterial Internalization by Epithelial Cells Is Promoted Independently by Decay-Accelerating Factor and Carcinoembryonic Antigen-Related Cell Adhesion Molecule Binding and Does Not Require the DraD Invasin

Abstract: The Dr family of Escherichia coli adhesins are virulence factors associated with diarrhea and urinary tract infections. Dr fimbriae are comprised of two subunits. DraE/AfaE represents the major structural, antigenic, and adhesive subunit, which recognizes decay-accelerating factor (DAF) and carcinoembryonic antigen (CEA)-related cell adhesion molecules (CEACAMs) CEA, CEACAM1, CEACAM3, and CEACAM6 as binding receptors. The DraD/AfaD subunit caps fimbriae and has been implicated in the entry of Dr-fimbriated E. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 53 publications
(97 reference statements)
3
54
0
Order By: Relevance
“…In addition, β1 integrins confer bacterial internalisation involving the microtubules system and caveolae (Guignot et al, 2001;Korotkova et al, 2008). Within the host cell, Afa/Dr appears to promote intracellular multiplication in a similar manner as has been described for type 1 fimbriae (Goluszko, Popov, et al, 1997;Jouve et al, 1997).…”
Section: Afa/dr Adhesinsmentioning
confidence: 67%
“…In addition, β1 integrins confer bacterial internalisation involving the microtubules system and caveolae (Guignot et al, 2001;Korotkova et al, 2008). Within the host cell, Afa/Dr appears to promote intracellular multiplication in a similar manner as has been described for type 1 fimbriae (Goluszko, Popov, et al, 1997;Jouve et al, 1997).…”
Section: Afa/dr Adhesinsmentioning
confidence: 67%
“…Lipid rafts play a role in the cell entry of Dr-and F1845-positive Afa/Dr DAF/CEACAMs DAEC into Caco-2/TC7 cells, since the ganglioside GM1 and VIP21/caveolin are recruited around adhering bacteria, and extraction of the membrane cholesterol with methyl-beta-cyclodextrin disorganizes the membrane lipid rafts and inhibits the cell entry of Afa/Dr DAF/CEACAMs DAEC (536,537). It is important to note that it has been established that the cell entry of Afa/Dr DAF/CEACAMs DAEC into epithelial cells is triggered by their major adhesin subunits E (538,539). The role of the D subunits of Afa/Dr DAF/CEACAMs DAEC, known as invasins (540,541), in the entry into epithelial cells remains controversial (542)(543)(544)(545)(546)(547).…”
Section: Cell Interaction Cell Entry and Intracellular Lifestylementioning
confidence: 99%
“…We used ATCC E. coli strain 25922, which possesses Class II P-fimbriae [27]. Previous studies indicated that various strains of E. coli with type 1 fimbriae interact with CEA and other human CEACAM family members through the Afa/Dr family of adhesins [28][29][30]. We have not examined the binding of the E. coli ATCC 25922 strain to CEA.…”
Section: Discussionmentioning
confidence: 99%